Новые полевкозубые Cricetodontinae (Rodentia, Cricetidae) из валезия Евразии и некоторые вопросы надродовой систематики подсемейства - Топачевский, В.А.; Скорик, А.Ф. (Вестник зоологии, 1988)
Systematic position of Valesian vole-toothed primitive Cricetodontidae of Eurasia is outlined. In accordance with recent Hesperomyinae of the New World system, a new tribe, Microtocricetini trib. n., is established clearly to distinguish by M3 and M1 Microtinae-like characters, along with the presence on all of constant root teeth of some primitive peculiarities characteristic to Cricetodontinae, not Cricetinae. Two new genera are established: Sarmatomys gen. n. from middle Sarmat of the SW European part of the USSR, and Tsaganocricetus gen. n. from possible analogs of North Kazakhstan Valesian. At least two principal evolutionary trends are shown for the tribe: with and without cement, representing clear parallelism with Microtinae.